Television and strategies for scheduling hearings for sale in Mexico Case study: talk show de Laura Bozzo - Montoya-Dávila, Alicia Eloína (Universidad Autónoma de Tamaulipas, 2011)
Research shows how television, and in particular the company Televisa, by the process of implementing its segmented television formats and genres to the audience, mainly by sex, age and socioeconomic status, to provide its advertisers strategic areas so that these approach their particular target, by reaching millions of people via television through the segmentation of the market. In this way, television and trade marks form a binomial aproachl in order to capture consumers in a process in which the viewer is the least important, what is sought are the benefits of capturing the audience to make consumer and keep repeating the same stereotypes. The talk show hosted by Laura Bozzo on Televisa’s Channel 2 is the point of analysis for reflection.